(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Coconut milk yoghurt, rich in healthy fats, offers a sustainable alternative to dairy. Converting it into powder enhances shelf life, versatility, and probiotic retention for diverse food applications. This study evaluates the effects of spray-drying (SD) and freeze-drying (FD) on the physicochemical, microbiological, and sensory properties of coconut milk-based yoghurt (CMY) compared to dairy yoghurt (DY). Yoghurt powders were prepared by diluting the yoghurts with 64% distilled water and 6% maltodextrin for SD processing, conducted at 150°C inlet and 65–70°C outlet temperatures. For FD, liquid yoghurts were frozen overnight and lyophilized under vacuum at -50°C for four days. Analysis revealed that dried CMY exhibited significantly higher soluble solids and lactic acid levels than dried DY (<0.72%) in both drying treatments. Although protein content in dried CMY powders is significantly lower (<23%) compared to DY powders (27%), the LAB counts were consistently higher in CMY samples. Significant differences were noted in colour parameters (b*), though no differences were observed for L* and a*. All dried yoghurts produced microbiologically safe powders, with yeast, mould, and coliform counts within acceptable limits. Sensory evaluation by 60 panellists using a 9-point hedonic scale indicated greater acceptance for CMY over DY, with SD powders preferred over FD powders. In conclusion, CMY is more preferred over DY for producing high-quality yoghurt powders with enhanced probiotic retention, better sensory appeal, and improved functional properties.